2014
DOI: 10.1039/c3tb21636e
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR aided design of molecularly imprinted adsorbents for selectively preparative separation of erythromycin

Abstract: Based on the 13C chemical shift changes, the optimal monomer of MAA was selected and the rational binding sites were predicted. The resultant materials show good selectivity for erythromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Investigations involving template–monomer complex studies have employed different methods, basis sets and levels of theories on several occasions. The majority of these studies employed DFT methods [ 124 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ,…”
Section: The Pre-polymerization Stagementioning
confidence: 99%
“…Investigations involving template–monomer complex studies have employed different methods, basis sets and levels of theories on several occasions. The majority of these studies employed DFT methods [ 124 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ,…”
Section: The Pre-polymerization Stagementioning
confidence: 99%
“…Andersson et al used this technique to optimize the template-functional monomer proportion. [104] Simple 13 C-NMR alone had not been used for the evaluation of the template-functional monomer interaction, until Zhang et al [105] reported a study where it was utilized to evaluate the interactions between antibiotic erythromycin (ERY) and a set of functional monomers, with the choice of MAA as the optimal one. The rational binding sites were predicted based on chemical shifts changes in ERY structure.…”
Section: Nmr Techniques Aiding Mip Productionmentioning
confidence: 99%
“…Since the idea of molecular imprinting was first put forward by Pauling in 1940s [43], over the past decades, it is well known that molecular imprinting is a very promising and rapidly evolving technology, with many possible applications such as preparative analytical separations [44][45], enzyme-like catalysis [46][47], solidphase extractions [48][49], chemical sensors [50][51] and drug delivery [52][53], etc. Molecular imprinting has proven to be particularly successful for small molecules.…”
Section: Photonic Crystalsmentioning
confidence: 99%